To solve the system by substitution, we start with the first equation:
X = 5
Next, we substitute this value of X into the second equation:
5 + y = 12
Now, we can solve for y by subtracting 5 from both sides:
y = 12 - 5
y = 7
So the solution to the system is X = 5 and y = 7.
Solve each system by substitution
X = 5
X + y = 12
7 answers
Solve each system by substitution
Y = 5
-3x + 4y = 8
Y = 5
-3x + 4y = 8
To solve the system by substitution, we start with the first equation:
Y = 5
Next, we substitute this value of Y into the second equation:
-3x + 4(5) = 8
Simplifying, we have:
-3x + 20 = 8
Now, we can solve for x by subtracting 20 from both sides:
-3x = 8 - 20
-3x = -12
Dividing by -3, we get:
x = -12 / -3
x = 4
So the solution to the system is x = 4 and Y = 5.
Y = 5
Next, we substitute this value of Y into the second equation:
-3x + 4(5) = 8
Simplifying, we have:
-3x + 20 = 8
Now, we can solve for x by subtracting 20 from both sides:
-3x = 8 - 20
-3x = -12
Dividing by -3, we get:
x = -12 / -3
x = 4
So the solution to the system is x = 4 and Y = 5.
Solve each system by substitution
y=-3x
4x - 2y = -20
y=-3x
4x - 2y = -20
To solve the system by substitution, we start with the first equation:
y = -3x
Next, we substitute this value of y into the second equation:
4x - 2(-3x) = -20
Simplifying, we have:
4x + 6x = -20
Combining like terms, we get:
10x = -20
Dividing by 10, we have:
x = -20 / 10
x = -2
Now, we substitute this value of x back into the first equation to solve for y:
y = -3(-2)
Simplifying, we have:
y = 6
So the solution to the system is x = -2 and y = 6.
y = -3x
Next, we substitute this value of y into the second equation:
4x - 2(-3x) = -20
Simplifying, we have:
4x + 6x = -20
Combining like terms, we get:
10x = -20
Dividing by 10, we have:
x = -20 / 10
x = -2
Now, we substitute this value of x back into the first equation to solve for y:
y = -3(-2)
Simplifying, we have:
y = 6
So the solution to the system is x = -2 and y = 6.
Solve each system by substitution
Y = -3x + 4
Y = 4x - 10
Y = -3x + 4
Y = 4x - 10
To solve the system by substitution, we set the two equations equal to each other:
-3x + 4 = 4x - 10
Next, we group the x terms on one side and the constant terms on the other side:
4 + 10 = 4x + 3x
14 = 7x
Now, we solve for x by dividing both sides by 7:
x = 14 / 7
x = 2
Now that we have the value of x, we substitute it back into one of the original equations to solve for y. Let's use the first equation:
y = -3(2) + 4
y = -6 + 4
y = -2
So the solution to the system is x = 2 and y = -2.
-3x + 4 = 4x - 10
Next, we group the x terms on one side and the constant terms on the other side:
4 + 10 = 4x + 3x
14 = 7x
Now, we solve for x by dividing both sides by 7:
x = 14 / 7
x = 2
Now that we have the value of x, we substitute it back into one of the original equations to solve for y. Let's use the first equation:
y = -3(2) + 4
y = -6 + 4
y = -2
So the solution to the system is x = 2 and y = -2.